Plasma-based preparation of polyaniline/graphene and polypyrrole/graphene composites for dye-sensitized solar cells as counter electrodes. Issue 4 (3rd April 2018) - Cogal, Sadik; Ali, Abdulrahman K.; Erten-Ela, Sule; Celik Cogal, Gamze; Kulicek, Jaroslav; Micusik, Matej; Omastova, Maria; Oksuz, Aysegul Uygun
ABSTRACT: This study presents the preparation of graphene (GR) nanocomposites with polyaniline (PANI) and polypyrrole (PPy) through the fast, versatile and environmentally friendly process of radio frequency (RF)-plasma polymerization. Morphological characterization of the nanocomposites is performed using scanning electron microscopy (SEM) and shows that the PANI and PPy conducting polymers coated the GR surface. The surface properties of the GR nanocomposites are determined using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). The prepared GR nanocomposites are then used as counter electrodes in dye-sensitized solar cells (DSSCs). The conversion cell efficiencies for iodine-doped DSSC samples are found to be 0.086%, 5.41%, and 5.60% for I2 -PANI, I2 -PANI-GR and I2 -PPy-GR, respectively, while the corresponding undoped samples reaches power conversion efficiencies of 3.82%, 1.30%, and 0.077% for PPy-GR, PANI-GR and PANI, respectively. The incident photon-to-current efficiency (IPCE) of iodine-doped composite-based DSSCs is significantly enhanced.